Heart rate and blood lactate in 400 m flat and 400 m hurdle running: a comparative study - Gupta, S.; Goswami, A.; Mukhopadhyay, S. (Indian Journal of Physiology and Pharmacology, 2000)
This study was conducted on a group of male sprinters (n = 8) to compare heart rate (HR) and blood lactate (La) response in 400 m flat and 400 m hurdle running during weekly trial race. Durations of the flat and hurdle races were 51.65 +/- 1.51 and 58.27 +/- 1.97 sec respectively. Peak HR attained at the end of the flat and hurdle races were 192.4 +/- 5.3 and 193.6 +/- 4.1 beats/min, whereas, average HR during the events were 173.6 +/- 22.6 and 176.7 +/- 19.6 beats/min respectively. La level following the flat event (18.84 +/- 1.57 mmol/L) was found significantly (P < 0.05) higher than the post-hurdle race (16.14 +/- 1.97 mmol/L). The study indicates that cardiovascular stress is similar in both the events although flat race impose higher anaerobic glycolytic demand than hurdle run.